Further Properties of Trees with Minimal Atom-Bond Connectivity Index - Jianping Liu; Jinsong Chen (Abstract and Applied Analysis)
Let G=(V,E) be a graph the atom-bond connectivity (ABC) index is defined as the sum of weights ((du+dv-2)/dudv)1/2 over all edges uv of G, where du denotes the degree of a vertex u of G. In this paper, we determined a few structural features of the trees with minimal ABC index also we characterized the trees with dia[T]=2 and minimal ABC index, where [T] is induced by the vertices of degree greater than 2 in T and dia[T] is the diameter of [T].